Dynamic computable general equilibrium simulation of agricultural greenhouse gas emissions in China. (15th April 2022) - Zhang, Xiaoxuan; Wu, Leying; Ma, Xiaozhe; Qin, Yaochen
Abstract: Climate change is an urgent global issue, and the agricultural sector is one of the main contributors to greenhouse gas (GHG) emissions. In order to accurately analyze agricultural GHG emissions, this study constructed a dynamic computable general equilibrium model of Chinese agriculture. We aimed to examine the trends and structure of agricultural GHG emissions, and grain production in China. Results show that (i) China's agricultural CO2 emissions will increase from 47.77 MtC in 2008 to 239.99 MtC in 2050. The input of agricultural materials is the primary source for this rise. (ii) Non-CO2 GHG emissions contribute the most to agricultural GHG, which will reach 2214.55 MtC in 2050. (iii) The total agricultural GHG emissions in China will maintain an overall upward trend from 2008 to 2050, increasing from 220 MtC in 2008–2413.64 MtC in 2050 with an average annual growth rate of 5.87%. (iv) GHG emissions from grain production will reach 919.09 MtC by the year 2050. GHG emissions per grain production and emissions per area will increase to 343.81 kgC/t, and 4.46 tC/ha by the year of 2050, respectively. These findings carry several policy implications to China's agriculture low-carbon development, such as improve the agricultural materials utilization efficiency, optimize manure management and treatment, and promote organic planting technology.